REFLECTION OF INTERNATIONAL STANDARDS IN THE FIELD OF LABOR MIGRATION IN THE NATIONAL LEGISLATION OF UZBEKISTAN - Ulugbek S. Bozorov (International Scientific and Current Research Conferences, 2022)
The expression of international standards in the field of labor migration in the national legislation of Uzbekistan was analyzed using theoretical and practical examples and statistical data.